RISMA AND AN INSIGHT OF IDEOLOGY IN POLITICAL POWER NARRATIVE - Indrayani, Inri Inggrit (Institute of Research and Community Outreach - Petra Christian University, 2015)
This study aims to determine the discourse in Tri Rismaharini?s utterances as the first female mayor of Surabaya in a prominent talk show program. Woman with a strategic position in political domain is a rare phenomenon in a patriarchal culture. Risma is phenomenal one since not a party cadre, could be a major. As the public support becomes immensely increase of Risma?s leadership. She was confronted a conflict of interests between political parties?s and the public?s. This condition raised issues about Risma?s resignation. In an interview on a private television, Risma revealed about her feeling as leader of the city. How Risma conceives political power? How Risma practices political power? How she engages people to understand and be involved toward her policies ? What about her political ideology ? Risma?s utterances on the program as a form of social act are interesting to be assessed. The method of this study is critical discourse analysis of Teun van Dijk. Van Dijk divides the analysis into three main parts which are the analysis of social, cognitive and discourse analysis. These analysis stages are used to examine the discourse in conversation or texts produced by a communicator. The analysis shows Risma puts political power as a divine mandate/transcendentalism. Secondly as women, Risma has implemented morality and justice as ethical politics further demonstrates masculinity through totality and accepts authority.